SUBJECTIVE WELL-BEING PERAWAT YANG BEKERJA DI RS JIWA PROF. DR. SOEROJO MAGELANG - Desi, Desi; Tanti, Tanti; Ranimpi, Yulius Yusak (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2019)
Living a happy life is everyone's dream. Happiness in psychology is termed Subjective Well-Being (SWB). SWB is a cognitive evaluation (life satisfaction) and affective (positive and negative effects). Nurses need to have a high Subjective Well-being in order to maximize the service of nurses in hospitals. The purpose of this study was to determine the SWB level of nurses working in mental hospitals RS. Dr. Soerojo Magelang. The method used is descriptive quantitative survey approach using a self-evaluation questionnaire that has been patented (has been adapted, modified, and changed into Indonesian). The self-evaluation questionnaire includes an adaptation of the Scale of Positive and Negative Experience (SPANE) and The Satisfaction With Life Scale (SWLS) questionnaire. Data were processed using SPSS to test variables with a significance level of 0.05. For the level of well-being in the measurement of affect (positive and negative), 142 (54.0%) respondents often experience positive affect and in the measurement of life satisfaction, as many as 156 (59.3%) have high life satisfaction.